2020
DOI: 10.1002/jcla.23250
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and hematological parameters in pregnant women

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…19 Por lo anterior, se permite comprender que en el embarazo fisiológico podría existir una respuesta hipertensora no aguda, expresada por un aumento del tono simpático. 13 La epinefrina se encuentra aumentada de un modo directamente proporcional a la función simpática, al ser esta catecolamina la principal indicadora del sns. 16 Por otro lado, hubo una correlación negativa moderada entre el sd y las plaquetas en el grupo de mujeres sanas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…19 Por lo anterior, se permite comprender que en el embarazo fisiológico podría existir una respuesta hipertensora no aguda, expresada por un aumento del tono simpático. 13 La epinefrina se encuentra aumentada de un modo directamente proporcional a la función simpática, al ser esta catecolamina la principal indicadora del sns. 16 Por otro lado, hubo una correlación negativa moderada entre el sd y las plaquetas en el grupo de mujeres sanas.…”
Section: Discussionunclassified
“…Únicamente un estudio realizado por Al-Shafei y Cols., en el 2020 demostró que existe una asociación positiva entre el volumen plaquetario medio (vpm) con la actividad simpática cardiaca, y una asociación negativa con la actividad parasimpática cardiaca en mujeres embarazadas. 13 El objetivo del presente estudio es explorar las asociaciones entre parámetros clásicos de la vfc influenciadas por la condición neuroinflamatoria de la preeclampsia y valores de parámetros hematológicos en embarazadas normotensas y con preeclampsia.…”
Section: Introductionunclassified
“…In addition, there is an increase in the number of myelocytes and metamyelocytes which indicate the increased level of activity in the bone marrow and erythropoiesis during pregnancy. In the first and second trimesters there is also a decrease in the lymphocyte count, compared to an increase in the third trimester (Chandra et al, 2012;Al-Shafei et al, 2020). Studies have also shown that platelet counts decrease in pregnancy, mainly in the third trimester.…”
Section: Changes In the Hematologic Systemmentioning
confidence: 99%
“…Changes in appetite, the occurrence of anemia due to a decrease in stomach acidity, especially in the rst trimester as a result of a decrease in intrinsic factor and decrease in vitamin B12 synthesis, impaired stomach movements and constipation are main changes in the gastrointestinal system (16)(17)(18)(19). Pregnancy leads to blood changes, including decreased red blood cell volume, hemoglobin, and serum protein concentration (19)(20)(21)(22)(23). In the respiratory system, the lungs move upwards, which results in the feeling of shortness of breath (10,(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%